Blame and Culpability in Children's Narratives of Child Sexual Abuse. (21st January 2020) - Ellis, Katie
Abstract : Though child sexual abuse (CSA) is a global problem, victims are treated differently across the world. In the UK, there is a dominant assumption that victims are passive, which risks further marginalising those who do not identify themselves in line with prominent understanding of 'vulnerability'. Drawing upon ethnographic fieldwork and in‐depth interviews, this paper shares the perspectives of girls who were placed in secure accommodation for their own protection, owing to professional concerns of CSA. Despite their experiences being reported almost identically in their files, this sensitive research shows that girls understood and narrated their journeys in strikingly different ways. Each shared complex relationships with their abuser and admitted to absconding with them on multiple occasions. Despite disparate narratives, the girls unanimously rejected being labelled as 'vulnerable' and instead felt that they were responsible for the abuse that they had endured. I argue that limited understanding of CSA problematises girls who claim sexual agency, meaning that they are consequently forced to shoulder responsibility for their own exploitation. By sharing the voices of those who are usually unheard, this paper concludes by calling for a radical reframing of the way that victims are treated, both by professionals working with them and by policies written about them. 'This paper shares the perspectives of girls who were placed in secure accommodation for their own protection, owing to professional concerns of CSA' Key Practitioner Messages: Girls believed that professionals held them accountable for being sexually abused. The structural disadvantages of childhood meant that children sometimes relied on their abusers for food and shelter. Victims sometimes felt that their abuser was their only friend. Professionals sometimes mistook resilience for culpability.